2019
DOI: 10.3390/pr7080496
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dynamic Impact of CO2 Emissions and Economic Growth on Renewable Energy Production: Evidence from FMOLS and DOLS Tests

Abstract: Understanding the dynamic nexus between CO2 emissions and economic growth in the sustainable environment helps the economies in developing resources and formulating apposite energy policies. In the recent past, various studies have explored the nexus between CO2 emissions and economic growth. This study, however, investigates the nexus between renewable energy production, CO2 emissions, and economic growth over the period from 1995 to 2016 for seven Association of Southeast Asian Nations (ASEAN) countries. Ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 67 publications
3
10
0
Order By: Relevance
“…The negative coefficient of variable X1 reveals that the renewable energy variable has a negative and significant effect on CO 2 emission, and a one-unit increase in the rate of renewable energy in total energy consumed will lead to a decrease in CO 2 emission rates by 0.654, which is congruent with the findings achieved by [41]. Also, the negative coefficient of X2 means that biofuel production has a negative and strong impact on CO 2 emissions, and a one-unit increase in biofuel production will lead to a decrease in CO 2 by 0.983, which is in line with [42].…”
Section: Resultssupporting
confidence: 76%
“…The negative coefficient of variable X1 reveals that the renewable energy variable has a negative and significant effect on CO 2 emission, and a one-unit increase in the rate of renewable energy in total energy consumed will lead to a decrease in CO 2 emission rates by 0.654, which is congruent with the findings achieved by [41]. Also, the negative coefficient of X2 means that biofuel production has a negative and strong impact on CO 2 emissions, and a one-unit increase in biofuel production will lead to a decrease in CO 2 by 0.983, which is in line with [42].…”
Section: Resultssupporting
confidence: 76%
“…Modern technology can help to remove the harmful substances from Thar coal and also serve as a tool for energy efficiency both in production and consumption of technology is employed in the initial stages of renewable energy development in a country. The economy might face the pressure of increase installation costs, but, in the long run, positive coefficient value ensures that renewable energy would increase the economic growth along with the improved environment in the long term [76,78].…”
Section: Fully Modified Ordinary Least Square (Fmols)mentioning
confidence: 99%
“…Many recent and past studies (Bilgili et al, 2016;Dogan and Turkekul, 2016;Dong et al, 2018;Pata, 2018) investigating energygrowth relationships have confirmed this postulate; however, many studies (Charfeddine, 2017;Dogan and Turkekul, 2016;Khan et al, 2019) have doubted this relationship too. The EKC hypothesis implies that in the initial stage of growth, environmental pollution increases, and then at the later stages it starts declining (Alam et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 96%
“…This indicates that there is an inverted U-shape relation between growth and environmental deterioration supporting the EKC hypothesis. Although there have been several research investigations performed on the energy consumption-CO 2 emissions-economic growth-FDI nexus (Ahmad et al, 2019;Akadiri et al, 2019;Khan et al, 2019;Salahuddin et al, 2018), to the best of the author's knowledge no study have been undertaken in the context of Oman and UAE, which is very crucial for such investigation. This study will attempt to fill this gap.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation